Identificação de hidrocarbonetos de petróleo totais na costa do Nordeste do Brasil - Araújo, Kelvin Costa de (2023)
In August 2019, a major oil spill occurred, affecting the northeastern coast of Brazil. For over two years after the incident, traces of crude oil could still be found on the beaches, and to this day, little is known about the cause and impacts of this spill. In incidents of this nature, various contaminants can be introduced into the environment. Total Petroleum Hydrocarbons (TPHs), particularly Polycyclic Aromatic Hydrocarbons (PAHs), are a relevant class of organic contaminants known for their potential mutagenic and carcinogenic properties. To investigate the presence of these contaminants on the northeastern coast, we conducted water and oil sampling at critical points along a 430 km stretch of coastline, including 33 beaches in 4 states. The monitoring was conducted through semi-annual sampling for a year and a half. Water samples were classified as open sea, sheltered waters, and freshwater and estuarine waters. Oil samples were subjected to exposure processes in synthetic seawater, and the leached components underwent degradation. Direct analyses of the synchronous fluorescence matrix were performed, which were transformed into excitation and emission spectral matrices. This procedure maximizes the spectral domain and minimizes the acquisition of scattering signals. Spectral profiles of water samples modeled with PARAFAC revealed the presence of TPH contaminants such as naphthalene-like and dibenzothiophene-like compounds. Monitoring of the impacted region demonstrated that even after more than a year from the incident, the contaminants were still present in the water samples. In the oil samples, we identified the presence of five TPH derivatives, with a notable amount of perylene-like compound found in most of the studied samples. The proposed procedure for the degradation of these contaminants exhibited high efficiency, with complete degradation occurring in just two minutes.